2014
DOI: 10.1038/srep05551
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Intestinal Epithelium Cytochrome P450 Reductase are Prone to Acute Toxin-induced Mucosal Damage

Abstract: Cytochrome P450 (P450) enzymes are a superfamily of heme-containing enzymes involved in the metabolism of various endogenous compounds, including retinoids, glucocorticoids, and eicosanoids, that are postulated to participate in the maintenance and/or development of inflammatory and immune reactions in the intestinal mucosa. To investigate the role of P450 enzymes in intestinal inflammation and immunity, we took advantage of IE-Cpr-null mice, which are deficient in intestinal epithelium of NADPH-cytochrome P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…CPR expression was normal in other tissues examined in IECN mice. These mice are fertile and develop normally, although they show hypersensitivity to intestinal injury induced by ricin, a plant-derived toxin 75 , and dextran sulfate sodium, an agent used to induce colon inflammation in a commonly used animal model of experimental colitis 76 . The IECN mouse also showed large changes in intestinal gene expression in cholesterol biosynthesis and antigen presentation/processing pathways 77 .…”
Section: Regulation Of Intestinal Cyp Expression and Functionmentioning
confidence: 99%
“…CPR expression was normal in other tissues examined in IECN mice. These mice are fertile and develop normally, although they show hypersensitivity to intestinal injury induced by ricin, a plant-derived toxin 75 , and dextran sulfate sodium, an agent used to induce colon inflammation in a commonly used animal model of experimental colitis 76 . The IECN mouse also showed large changes in intestinal gene expression in cholesterol biosynthesis and antigen presentation/processing pathways 77 .…”
Section: Regulation Of Intestinal Cyp Expression and Functionmentioning
confidence: 99%
“…In contrast, it has been recently found that the loss of CPR expression in the enterocytes of IE-Cpr-null mice led to numerous gene expression changes in the small intestine, including upregulation of the major histocompatibility complex class II genes (D'Agostino et al, 2012). Furthermore, IE-Cpr-null mice were prone to acute mucosal damage in the small intestine induced by the ricin toxin, a finding in support of a role of microsomal P450 enzymes in mucosal homeostasis and immunity (Ahlawat et al, 2014). Thus, further studies are needed to define genomic changes in the colon resulting from the loss of CPR expression, to identify potential mechanistic links to the hypersensitivity to DSS-induced toxicity.…”
Section: Discussionmentioning
confidence: 98%